2018
DOI: 10.1021/acsearthspacechem.7b00153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photolysis on Absorption and Fluorescence Spectra of Light-Absorbing Secondary Organic Aerosols

Abstract: Excitation−emission matrices (EEMs) constructed from fluorescence measurements are increasingly used for the characterization of chromophoric dissolved organic matter (CDOM) and light-absorbing atmospheric organic aerosols known as brown carbon (BrC). There is a high uncertainty in the effect of BrC aerosols on climate because their optical properties depend on the amount of time they spent in the atmosphere. In order to aid in the quantification of BrC aerosols' contribution to radiative forcing, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 59 publications
7
46
0
Order By: Relevance
“…They suggested that photolysis, rather than hydrolysis, bleached SOA absorption due to degradation of nitrogen-containing chromophores. This conclusion was also confirmed by similar studies by Lee et al (2014) and Aiona et al (2018). In our study, the changes in the optical properties as a function of O/C ratio for tar balls upon photolysis are shown in Figure S15.…”
Section: Prediction Of Mixture Tar Ball Optical Properties Based On Dsupporting
confidence: 89%
“…They suggested that photolysis, rather than hydrolysis, bleached SOA absorption due to degradation of nitrogen-containing chromophores. This conclusion was also confirmed by similar studies by Lee et al (2014) and Aiona et al (2018). In our study, the changes in the optical properties as a function of O/C ratio for tar balls upon photolysis are shown in Figure S15.…”
Section: Prediction Of Mixture Tar Ball Optical Properties Based On Dsupporting
confidence: 89%
“…The decrease of absorbance confirm that COM are photo-bleached (Duarte et al, 2005). The subduction function of photolysis on absorbance is significant (Aiona et al, 2018). In POA (Fig.…”
Section: Effect Of Com Photo-degradation On Optical Propertiesmentioning
confidence: 53%
“…Three-dimensional excitation emission matrix (EEM) spectroscopy, which yields fluorescence intensities as a function of both excitation and emission wavelengths, has been widely applied to characterize chromophoric dissolved organic matter in terrestrial and oceanic systems 17 , 18 . However, the method has rarely been used for the analysis of complex organic matter in atmospheric aerosols 19 23 , particularly for marine aerosols. Classifications of organic matter with EEM spectra in SSA need to be employed in comparison with that in SSW, because their sources, chemical compositions, and transformation pathways are expected to be different from those in the marine aqueous environment.…”
Section: Introductionmentioning
confidence: 99%